2016
DOI: 10.18290/rpsych.2016.19.4-5en
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in prospective memory in young and older adults

Abstract: The main purpose of the present study was to investigate the relation between gender and prospective memory performance with respect to participants' age and the specific requirements of prospective memory tasks. Prospective memory performance was better for women compared to men in the older adult group. In the entire sample, women performed better than men on prospective memory tasks with an external cue. The possible influence of factors related to the gender role, personality, and perception on prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Men exhibit greater EBPM accuracy than women (Mmen=3.846 > Mwomen=3.036, t=2.791, p=0.004). This conclusion contradicts a recent study that reported no gender differences in young adult participants but showed women superior EBPM abilities in the elderly (4). It also contradicts earlier research that shows young adult women outperform men in EBPM performance (20).…”
Section: Ebpm Accuracy Performancecontrasting
confidence: 87%
See 1 more Smart Citation
“…Men exhibit greater EBPM accuracy than women (Mmen=3.846 > Mwomen=3.036, t=2.791, p=0.004). This conclusion contradicts a recent study that reported no gender differences in young adult participants but showed women superior EBPM abilities in the elderly (4). It also contradicts earlier research that shows young adult women outperform men in EBPM performance (20).…”
Section: Ebpm Accuracy Performancecontrasting
confidence: 87%
“…Previous research has found that there are individual variances in the types of gender that improve PM performance, even though it is still few in sum, and the results are not always consistent. The performance of Event-Based Prospective Memory (EBPM) is higher in women than men in the older adult group, while there is no difference in the young adult group (4). Then, previous research found that young adult males are better than women when it comes to Time-Based Prospective Memory (TBPM) performance (5).…”
Section: Introductionmentioning
confidence: 99%
“…PM performance and metacognitive control in PM tasks improve as school-age children grow up (Redshaw et al, 2018;Yang et al, 2011). On the contrary, female adults employ more strategies to memorize PM tasks (Penningroth & Scott, 2014) and show better PM performance than male adults (Palermo et al, 2016;Riess et al, 2016). Gender effect on PM has seldom been studied in typically developing children, and the results are mixed (Ceci & Bronfenbrenner, 1985;Cheie et al, 2021;Kliegel et al, 2013;Maylor & Logie, 2010;Yang, 2008).…”
Section: The Effect Of Implementation Intentions On Pm In Childrenmentioning
confidence: 99%